Peningkatan Literasi Sains Pada Mata Pelajaran IPAS Menggunakan Model Contextual Teahcing - Ananta Syakilla Abrisaputri; Abdullah; Dhini Mufti (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
This study aims to improve the scientific literacy of fifth-grade students in the science subject through the application of the Contextual Teaching and Learning (CTL) model. The method used is Classroom Action Research (CAR) with four stages: planning, implementation, observation, and reflection. The subjects of the study were 15 fifth-grade students of SDN 127/II Sungai Arang. Data were collected through science literacy tests, observation, and documentation. The results showed a significant increase in learning completeness from 40% in Cycle I to 100% in Cycle II. Teacher performance increased from 88.88% to 100%, while student activity in the excellent category increased from 6.66% to 60%. The CTL model has proven effective in creating meaningful learning by connecting science concepts with students' real lives, providing practical implications for improving the quality of science learning in elementary schools.